2013
DOI: 10.1080/13623699.2013.813109
|View full text |Cite
|
Sign up to set email alerts
|

Political violence, collective functioning and health: A review of the literature

Abstract: Political violence is implicated in a range of mental health outcomes, including PTSD, depression, and anxiety. The social and political contexts of people’s lives, however, offer considerable protection from the mental health effects of political violence. In spite of the importance of people’s social and political environments for health, there is limited scholarship on how political violence compromises necessary social and political systems and inhibits individuals from participating in social and politica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 129 publications
0
27
0
1
Order By: Relevance
“…The dominant explanation about radicalisation is that poverty, unemployment, discrimination, political isolation and cultural marginalisation lead to grievances, which in turn foster increased receptivity to political violence as a solution. 7 Adverse life events and poor civic engagement are associated with depression 12,13 and poor health 14,15 and are reported to engender extremism, 7,1618 suggesting some shared aetiologies for depression and extremism.…”
mentioning
confidence: 99%
“…The dominant explanation about radicalisation is that poverty, unemployment, discrimination, political isolation and cultural marginalisation lead to grievances, which in turn foster increased receptivity to political violence as a solution. 7 Adverse life events and poor civic engagement are associated with depression 12,13 and poor health 14,15 and are reported to engender extremism, 7,1618 suggesting some shared aetiologies for depression and extremism.…”
mentioning
confidence: 99%
“…Political violence simultaneously compromises individual, community, and government functioning (Hobfoll et al, 2007; Lykes et al, 2007; Martín-Baró et al, 1994; Robben, 2005; Sousa, 2013). Accordingly, healing from political violence is not just an individual imperative, but rather a communal process centered on the reestablishment of collective trust and social and political action (Ager et al, 2005; Summerfield, 2002).…”
Section: Introduction: Political Violence Neoliberalism and Mental mentioning
confidence: 99%
“…Following the COVID-19 pandemic, mental health has been highlighted as a global priority in response to the fallout of the crisis, with the toll of lockdown, loss of jobs, increase in domestic violence, and lower social support impacting the wellbeing and functioning of affected populations (Holmes et al ., 2020; UNHCR, 2020a; WHO, 2020). Research has shown that such crises, particularly when chronic, have an impact beyond the experience of the individual, affecting the functioning of families, communities, and wider social structures and socio-political systems (Sousa, 2013; Somasundaram, 2014). Despite major advances in the development and implementation of interventions in responding to crises and emergencies, there remain significant gaps in the evidence-base for public mental health responses that are sufficiently contextualized to this collective suffering.…”
mentioning
confidence: 99%